Synthesis and physicochemical analysis of pyrazinib and quininib prodrugs and discovery of novel cysteinyl leukotriene receptor 1 antagonists - Qaisar, Alina (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2025)
Gastrointestinal cancers, particularly oesophageal adenocarcinoma (OAC), are aggressive diseases with a poor 5-year survival rate of less than 20%. Current treatment for OAC is neoadjuvant therapy, including chemotherapy and chemoradiation which achieve a complete pathological response in only 30% of patients. The lack of validated biomarkers to predict therapy response and the absence of approved radiosensitisers for preoperative use highlight the need for novel treatment strategies. Similarly, uveal melanoma (UM), a malignancy of the eye prone to metastasis, requires innovative therapeutic approaches. A significant challenge in developing treatments for these cancers is the poor water solubility of many promising drug candidates, which limits their bioavailability and efficacy. This thesis focuses on improving the water solubility and chemical stability of two promising anti-cancer agents, pyrazinib and quininib, which are under development as adjunct treatments for OAC and metastatic uveal melanoma (MUM), respectively. Both compounds suffer from suboptimal physicochemical properties, particularly poor water solubility, which restricts their in vivo preclinical testing and clinical delivery. Pyrazinib was identified through a phenotype-based screen in vivo in zebrafish and discovered as a promising radiosensitiser in vitro in an isogenic OAC radioresistance model. While pyrazinib demonstrates good stability over a range of pH values, it has poor aqueous solubility. Chapter 2 focuses on the enhancement of water solubility of pyrazinib by designing and synthesising prodrugs of pyrazinib aimed at improving aqueous solubility. Various synthetic routes were explored, including Perkin condensation and metal-catalysed reactions, to optimize the yield and efficiency of pyrazinib synthesis. This chapter also details the development of amino acid prodrugs of pyrazinib, investigating their chemical stability, enzymatic activation, and water solubility. Moreover, the synthesised prodrugs were investigated for their radiosensitising activity in vitro in isogenic OAC radio-resistance cell line. Furthermore, in this thesis, identification of novel cysteinyl leukotriene receptor 1 (CysLT1) antagonists were carried out by utilising a ligand-based virtual screening (LBVS) technique. Chapter 3 outlines the computational methodologies employed, including protein preparation, water analysis using 3D RISM, and ligand-protein interaction mapping. LBVS led to the discovery of potential CysLT1 antagonists which were subsequently evaluated for their binding affinity and antagonist activity through in vitro assays. This chapter provides a comprehensive analysis of the interaction dynamics between the identified hits and the CysLT1 receptor, offering insights into their therapeutic potential. Quininib (Q1) was identified through a phenotype-based screen in vivo in zebrafish and discovered as an inhibitor of LTD4-induced activation of the human CysLT1 receptor but suffers from poor water solubility and stability. Chapter 4 covers the synthesis of quininib and its analogues (Q series: Q7, Q28 and Q29), focusing on improving water solubility and chemical stability. Biological evaluations, including cytotoxicity and antiproliferative assays, assessed the anticancer efficacy of these analogues in MUM cancer cell lines, demonstrating their potential as effective anticancer agents. Furthermore, the in vivo toxicity and anti-angiogenic activity of quininib analogues, pyrazinib amino acid prodrugs and selected CysLT1 potent hit antagonists were evaluated using a zebrafish model. Chapter 5 highlights the suitability of the zebrafish model for preclinical drug screening, detailing the experimental protocols for assessing in vivo toxicity and inhibition of angiogenesis. The findings from these studies provide valuable insights into the safety and efficacy of the synthesised compounds, supporting their potential use in cancer treatment. Overall, this thesis presents novel research concerning the synthesis, physicochemical, and biochemical evaluation of pyrazinib and quininib analogues, aiming to improve water solubility and offer new therapeutic options for OAC and MUM. The findings support the potential use of these compounds in cancer treatment, addressing critical challenges in drug development for these formidable cancers.
APPROVED